The Structure of Formation of Historical Thinking in A Future Teacher of History in The Process of Studying Historical Disciplines - Rimma Ramilevna Zamilova (Zien Journals, 2021)
The problem of the formation of historical thinking in the theory and practice of training a future history teacher is considered. The essence, functions, and features of the teacher's historical thinking in the study of historical disciplines. Thanks to methodological techniques, special organizational forms of teaching, game modeling and other active methods of teaching history, historical thinking is formed. The author notes that the technology of game modeling fits very organically into the educational process, does not affect the content of training, allows the most effective way to achieve the predicted learning outcomes and reveal the potential of each student
Keywords: History; humanization; pedagogical education; teaching methods